2022
DOI: 10.1073/pnas.2106379119
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of SARS-CoV-2 proofreading exoribonuclease ExoN

Abstract: High-fidelity replication of the large RNA genome of coronaviruses (CoVs) is mediated by a 3′-to-5′ exoribonuclease (ExoN) in nonstructural protein 14 (nsp14), which excises nucleotides including antiviral drugs misincorporated by the low-fidelity viral RNA-dependent RNA polymerase (RdRp) and has also been implicated in viral RNA recombination and resistance to innate immunity. Here, we determined a 1.6-Å resolution crystal structure of severe acute respiratory syndrome CoV 2 (SARS-CoV-2) ExoN in complex with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 54 publications
(69 reference statements)
6
80
0
2
Order By: Relevance
“…Further, the RNA-binding site is partially occluded by the lid fragment (Thr35-Lys47), which additionally buries the nsp10-binding site. It has been shown that Lys9 of the nsp14 is critical for exonuclease activity ( Moeller et al., 2022 ). This residue is not visible in our electron density.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the RNA-binding site is partially occluded by the lid fragment (Thr35-Lys47), which additionally buries the nsp10-binding site. It has been shown that Lys9 of the nsp14 is critical for exonuclease activity ( Moeller et al., 2022 ). This residue is not visible in our electron density.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that IBV Nsp14 inhibited the chIFN-γ-activated JAK-STAT signaling pathway in a dose-dependent manner. The CoV Nsp14 protein acts as a bifunctional protein, with the ExoN domain being crucial for CoV replication proofreading activity and the N7-MTase domain being involved in viral mRNA capping [ 38 , 39 ]. Recombinant MHV using reverse genetic techniques demonstrated that guanine N7-methylation of CoV Nsp14 helps the virus evade the type-I-IFN-mediated immune response and pathogenesis in mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a self‐assembled monolayer for matrix‐assisted laser desorption ionization (SAMDI) mass spectrometry assay indicates that Nsp14/Nsp10 requires a 3′OH, confirming that the enzyme acts in a 3′–5′ direction and that the first nucleotide likely is digested before proceeding with subsequent activities [ 42 ]. Comparing the structural coordinates of Nsp14 in metal‐free ( 7MC5 , [ 43 ]), metal B site bound ( 7DIY , [ 44 ]), and substrate and metal A and B site bound ( 7N0B , [ 36 ]) states, reveals that the engagement of substrate and metals results in a conformational change surrounding the active site and the substrate‐binding site (Fig 3B , right). While the structural studies do not fully detail the mechanism of Nsp14 exonuclease activity, these recent structures provide the framework for future structural studies.…”
Section: Nsp14mentioning
confidence: 99%